THEORETICAL ASPECTS OF MANAGING THE ENERGY SUPPLY POTENTIAL OF SUSTAINABLE REGIONAL DEVELOPMENT - Shkoda, Mariana S.; Oleshko, Anna A. (Journal of Strategic Economic Research, 2023)
The article presents the results of research on the theoretical aspects of energy supply management in conditions of sustainable development. The concept and structural components of energy saving of enterprises in the conditions of sustainable development are studied, which is presented as a set of measures aimed at reducing energy losses, which comes both from external sources and is used inside the production system and requires the use of energy-saving equipment, energy-saving technologies of production, transportation and storage. The relationship between the categories: management of "energy potential", "resource potential", and "energy saving potential" is determined. This categorical series was studied and the concept of the energy saving potential of the enterprise in conditions of sustainable development was determined, which is presented as the realization of the energy potential as a set of reserves for reducing energy consumption, the ability and adaptability of the object management system to rationally use fuel and energy resources. As a result of the study, it was proved that the management of energy supply in conditions of sustainable development, aimed at ensuring the rational use of available energy resources, is based on conducting energy technological measurements, inspections, analyzing energy use and implementing an automated system for possible energy-saving measures.